Ekstraksi dan Pemurnian Alginat dari Sargassum filipendula Kajian dari Bagian Tanaman, Lama Ekstraksi dan Konsentrasi Isopropanol - Zailanie, Kartini; Susanto, Tri; Widjanarko, Simon B. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2001)
The objective of this research was to obtain the best treatment combination between plant’spast and length of extraction time and also purification by using isopropanol in order to obtainfrom seaweed thallus of Sargassum filipendula. This research used a Block Random Design having two factors. The first factor was plant’spart i.e. top, whole, lower end, leaves and the second factor was length of extraction time: 1 hour,2 hours and 3 hours. The best result from the two combinations was applied in the second phase ofresearch. The factors studied in the second phase were condition of seaweed (fresh and dried) andpurified by using isopropanol of 85%, 90% and 95%. Parameters evaluated were yield, watercontent, viscosity, ash content, Pb and Hg content, and effect of pH and heating on the product. The results showed that there were significant effect of the plant’s part to the yield and viscosity(α = 0,01). The length of extraction time significantly effected yield and viscosity. There were interaction between part of plant with the length of extraction time towards yield and viscosity ofalginate. The concentration of isopropanol did not have a significant effect to the product. Therewas a significant interaction between fresh and dry condition of the material and isopropanolconcentration towards viscosity. The best treatment was combination treatment of lower end part and wet condition that wasextracted for 2 hours and purified by using isopropanol 95% to produce 26.96% of alginate salt,14.21 cps of viscosity, and 3.25% ash content. The Hg content was 0.27 ppm and 6.30 ppm pf Pbwhich is still under the limit of government regulation.Keywords: extraction, purification, seaweed